Early abdomino-perineal pull-through vaginoplasty - Ilhan Ciftci; Ayhan Tastekin; Ali Annagur; Mustafa Koplay (Wolters Kluwer Medknow Publications, 2013)
Vaginal agenesis is known as one of the Mόllerian anomalies. Mόllerian anomalies occur during gonadal development and differentiation, and may lead to complex outcomes. McKusick-Kaufman syndrome (MKS) is an autosomal recessive multiple malformation syndrome characterized by Mόllerian anomalies with hydrometrocolpos (HMC) and postaxial polydactyly (PAP). We report a case of a female newborn that developed hydronephrosis and respiratory distress due to compression of the cystic mass and underwent surgery on postpartum day 3. Pull-through vaginoplasty was performed with an abdomino-perineal approach. We report the unique treatment approach in this case.